Observed Differences in Social Behaviors Exhibited in Peer Interactions Between Youth With Spina Bifida and Their Peers: Neuropsychological Correlates - Holbein, Christina E. (J Pediatr Psychol, 2015)
Objective To identify differences in social behaviors in observed peer interactions between children with spina bifida (SB) and peers, and to examine neuropsychological correlates of these differences. Method A total of 100 youth (aged 8–15 years) with SB and peers participated in video-recorded interaction tasks, which were coded for interaction style, affect, and collaboration. Children with SB also completed a neuropsychological test battery. Results Children with SB demonstrated less adaptive social behaviors in peer interactions, particularly within the interaction style domain. Observational items found to be different between children with SB and their peers were best predicted by social language and attention abilities. Conclusions Children with SB exhibit a less adaptive interaction style and lower levels of social dominance but are comparable with typically developing peers on other social behaviors. The observed group differences may have a neuropsychological basis.